Acute Physiological Effects of Energy Drinks on Cardiovascular Endurance, Blood Pressure, and Heart Rate in Collegiate Athletes - Rey L. Rabuya; Joseph Lobo; Arvin A. Andacao; Leonard Sydrick H. Pajo; Hazel Joyce M. Cariaga (CV. FOUNDAE, 2025)
Background: Energy drinks are commonly consumed by athletes due to their caffeine and stimulant content, which is believed to enhance performance. Previous research suggests benefits for anaerobic power and reaction time, but their effects on cardiovascular endurance and physiological responses remain inconclusive.Aims: This study aimed to examine the acute effects of energy drink consumption on cardiovascular endurance, blood pressure, and heart rate among collegiate athletes in the Philippines.Methods: Using a one-group pretest-washout-posttest design, 21 collegiate athletes (12 males, 9 females) participated. Cardiovascular endurance was assessed using the beep test. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using a digital sphygmomanometer (Omron 10 Series BP7450), while heart rate (HR) and heart rate recovery (HRR) were monitored digitally. Participants underwent a pretest, consumed 330 ml of energy drink, completed a washout period, and then performed a post-test. The Shapiro-Wilk test was used to assess normality, and paired sample t-tests determined pre–and post-test differences.Result: Energy drink intake did not significantly improve cardiovascular endurance (p > .05). However, significant increases in DBP (p = .040) and HR (p = .029) were observed in males. At the same time, females showed a significant rise in SBP (p = .032). HRR significantly improved in females (p = .031), indicating a possible short-term recovery benefit. Combined results showed a significant increase in DBP (p = .021), while HRR approached significance (p = .055).Conclusion: Although no enhancement in cardiovascular endurance was observed, energy drinks acutely influenced cardiovascular markers, raising blood pressure and heart rate in males and enhancing HRR in females. The absence of a control group and uncontrolled variables, such as caffeine metabolism, hydration, and socioeconomic factors, limit causal conclusions. These findings suggest the need for sex-specific guidance when using energy drinks. Future randomized trials with larger samples are recommended.